Isotopic signatures for natural versus anthropogenic Pb in high-altitude Mt. Everest ice cores during the past 800 years - Lee, K.; Hur, S.; Hou, S.; Nunes, Laurie; Hong, S.; Barbante, C.; Boutron, C.; Rosman, Kevin (Elsevier, 2011)
A long-term record, extending back 800 years (1205 to 2002 AD), of the Pb isotopic composition (206Pb/207Pb and 208Pb/207Pb) as well as Pb concentrations from high altitude Mt. Everest ice cores has the potential to identify sources and source regions affecting natural and anthropogenic Pb deposition in central Asia. The results show that the regional natural background Pb isotope signature (~1.20 for 206Pb/207Pb and ~2.50 for 208Pb/207Pb) in the central Himalayas was dominated by mineral dust over the last ~750 years from 1205 to 1960s,mostly originating from local sources with occasional contributions of long-range transported dust probably from Sahara desert and northwestern India. Since the 1970s, the Pb isotope ratios are characterized by a continuous decline toward less radiogenic ratioswith the leastmean ratios of 1.178 for 206Pb/207Pb and 2.471 for 208Pb/207Pb in the period 1990–1996. The depression of the 206Pb/207Pb and 208Pb/207Pb values during the rrespondingperiods ismost likely due to an increasing influence of less radiogenic Pb of anthropogenic originmainly from leaded gasoline used in South Asia (India aswell as possibly Bangladesh and Nepal). From1997 to 2002, isotopic composition tends to show a shift to slightly more radiogenic signature. This is likely attributed to reducing Pb emissions from leaded gasoline in source regions, coinciding with the nationwide reduction of Pb in gasoline and subsequent phase-out of leaded gasoline in South Asia since 1997. An interesting feature is the relatively high levels of Pb concentrations and enrichment factors (EF) between 1997 and 2002. Although the reason for this feature remains uncertain, it would be probably linked with an increasing influence of anthropogenic Pb emitted from other sources such as fossil fuel combustion and non-ferrous metal production.